Analysis of metal thin-film adhesion to parylene substrate for neural electrodes using tape test - Park, HyungDal; Choi, Won suk; Oh, SungHwan; Kim, Joohee; Kwak, Sung Soo; Kim, Yong-Jun; Seok, Seonho; KIM, JIN SEOK (2023년, 제25회 한국 MEMS학술대회, 2023)
This paper presents measurement and FEM (Finite Element Method) analysis of metal thin-film adhesion to parylene substrate for neural electrodes. A test sample was composed of patterned metal thin-films with 300 nm-thick gold and 30 nm-thick titanium on top of parylene substrate. To improve adhesion, CF4-based plasma treatment was applied before metal thin-film deposition. The adhesion was measured with the scotch tape test. Force exerted on the scotch tape was recorded as the function of displacement of the scotch tape. It was found that a peak was created in the measured force-displacement curve due to metal delamination. Metal thin-film adhesion was estimated 1.3 J/m2 by referring to the force peak and metal width at the force-displacement curve. Besides, the scotch tape test was simulated to comprehend the delamination behavior of the test through FEM modeling.